Pemetrexed for the treatment of non-small cell lung cancer. (August 2013) - Genova, Carlo; Rijavec, Erika; Truini, Anna; Coco, Simona; Sini, Claudio; Barletta, Giulia; Dal Bello, Maria Giovanna; Alama, Angela; Savarino, Grazia; Pronzato, Paolo; Boccardo, Francesco; Grossi, Francesco
Abstract : Introduction: Non-small cell lung cancer (NSCLC) is a major cause of cancer-related death worldwide. Although advanced NSCLC is still incurable, various anti-neoplastic agents have become available for the treatment of this disease.Pemetrexed, a multi-target folate antagonist, has improved the survival of non-squamous NSCLC patients. Currently, pemetrexed is approved for first-line treatment in combination with a platinum derivate, for second-line treatment as a single agent and, more recently, as maintenance treatment after first-line chemotherapy. Areas covered: The authors analyzed the state of the art of pemetrexed through a review of the literature. Clinical trials and meta-analyses involving pemetrexed in NSCLC were evaluated. Pemetrexed improved survival of non-squamous NSCLC in first-line, maintenance, and second-line treatments; this benefit is limited to non-squamous histology. Because pemetrexed has become part of the standard of care, current clinical trials are designed to compare it to other investigational combinations. Limited data on resectable disease are available, and additional clinical trials are being conducted. Expert opinion: Pemetrexed has shown effectiveness and a favorable toxicity profile. Histology-driven indications and the relationship of pemetrexed with thymidylate synthase expression suggest that a more precise definition of predictive biomarkers could be further investigated.